Analysis and Design of Solar Photo voltaic Grid Connected Inverter - Muddasani Satyanarayana; P. Satish Kumar (IAES Indonesian Section, 2015)
This paper presents common mode voltage analysis of single phase grid connected photovoltaic inverter. Many researchers proposed different grid tie inverters for applications like domestic powering, street lighting, water pumping, cooling and heating applications, however traditional grid tie PV inverter uses either a line frequency or a high frequency transformer between the inverter and grid but losses will increase in the network leading to reduced efficiency of the system. In order to increase the efficiency, with reduced size and cost of the system, the effective solution is to remove the isolation transformer. But common mode (CM) ground leakage current due to parasitic capacitance between the PV panels and the ground making the system unreliable. The common mode current reduces the efficiency of power conversion stage, affects the quality of grid current, deteriorate the electric magnetic compatibility and give rise to the safety threats. In order to eliminate the common mode leakage current in Transformerless PV systm two control algorithms of multi-carrier pwm are implemented and compared for performance analysis.The shoot-through issue that is encountered by traditional voltage source inverter is analyzed for enhanced system reliability. These control algorithms are compared for common mode voltage and THD comparisons. The proposed system is designed using MATLAB/SIMULINK software for analysis.